Meditation and lavender aromatherapy combinations reducing stress of health students - Endang Nurul Syafitri; Sang Ayu Nyoman Sri Ratmini; Wahyu Rochdiat Murdiono (Universitas 'Aisyiyah Yogyakarta, 2019)
Health students have been shown to have more stress than the general public. Student stress if left untreated can lead to health problems. previous studies have never measured a combination of meditation and lavender aromatherapy to reduce stress. This study aims to determine the decrease in stress of health students after being given a combination of meditation and lavender aromatherapy. Quasy Experiment pre test and post test of non equivalent control group. The sampling technique uses Quota sampling. The number of respondents was 40 people divided into two groups, namely 20 treatment groups and 20 controls. The bivariate test used is paired t-test with 95% CI value. Average stress score in the treatment group was 12.50 (normal stress) and in the control group of 14.60 (mild stress). The results of paired t-test in the treatment group obtained p value of 0.001 which means the difference in stress score before and after therapy with an average decrease of 3.20 points. In the control group there was a difference in stress score (p value = 0,000) with an average increase of 1.15 points. The combination of meditation and lavender aromatherapy effectively decreases the stress score of healthcare students. The combination of meditation and lavender aromatherapy can be a new standard for mental health nurses to manage stress on students.